The influence of psychological distance on work design behavior - Hodge, Jack H; Andrei, Daniela; Klonek, F.E. (2019)
Purpose: Based on the wealth of research suggesting jobs with enriched work designs (i.e., jobs with high autonomy, variety, significance, etc.) enhance work motivation and performance, this research contributes to a better understanding of factors that foster enriched work design behaviours (i.e., decisions made by stakeholders in the local context that shape the job design of others). Based on Construal Level Theory, we hypothesize that psychological distance between job designer and job incumbents is negatively related to enriching task allocation (i.e., deciding to allocate more tasks with enriched work characteristics to a job). Design/Methodology: We designed a vignette study to measure work design strategies in a sample of 207 participants recruited via Mturk. In the between-person experiment, we varied three levels of psychological distance between designer and job incumbent (no, low, and high psychological distance). We used multiple regression to test our hypothesis. Results: Preliminary results support the basic assumptions of our model; allocation of low-skill tasks is positively associated with psychological distance, and allocation of high-skill tasks is negatively associated with psychological distance. Limitations. Noted limitations of vignette studies include realism and generalizability. Research/practical implications: Our results may hold valuable insights for the practice of work design in contexts with a high degree of psychological distance (i.e., distributed teams, crowdsourcing). Originality/Value: Research on individual level antecedents to work design is rare, and to our knowledge, this is the first study that investigates the influence of psychological distance on work design behaviour.